2014
DOI: 10.1093/ntr/ntu281
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of PROP Taste Phenotype, Taste Receptor Genotype, and Oral Nicotine Replacement Use

Abstract: Introduction: Recommended dosage of oral nicotine replacement therapy (NRT) product is often not achieved in smoking cessation attempts. n-6-propylthiouracil (PROP) bitter taste phenotype may be a potential risk factor for non-adherence to oral NRT products due to their bitter taste. There is limited literature on this phenotype in the context of smoking and none in relation to oral NRT pharmacotherapy. Methods: The association of PROP taste phenotype with NRT usage and sensory response to products was examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In conclusion, it is becoming increasingly clear that PROP tasting is a complex phenotype influenced by a variety of factors including the functional interaction between TAS2R38 and the gustin gene that controls the taste bud trophic factor known as gustin protein [ 28 ], differences in messenger RNA expression in fungiform papillae [ 84 ], as well as environmental factors such as age and smoking [ 85 , 86 ]. Our recent work adds an additional dimension to our understanding of these phenotypic differences by focusing on the permissive role of the salivary Ps-1 protein and its constituent amino acid L-Arg in PROP taste responsiveness [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, it is becoming increasingly clear that PROP tasting is a complex phenotype influenced by a variety of factors including the functional interaction between TAS2R38 and the gustin gene that controls the taste bud trophic factor known as gustin protein [ 28 ], differences in messenger RNA expression in fungiform papillae [ 84 ], as well as environmental factors such as age and smoking [ 85 , 86 ]. Our recent work adds an additional dimension to our understanding of these phenotypic differences by focusing on the permissive role of the salivary Ps-1 protein and its constituent amino acid L-Arg in PROP taste responsiveness [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very little work has been done on the acute effects of smoking abstinence, although one study showed partial recovery of taste acuity following 12 h of smoking abstinence [ 132 ]. To our knowledge, the study by Ahijevych et al [ 57 ] is the only clinical trial to examine relationships between PROP tasting and smoking cessation in individuals with access to nicotine replacement therapy (NRT). Results showed that PROP non-tasters were more likely to use nicotine lozenges, which is consistent with the notion that oral nicotine exposure is less aversive to non-taster individuals.…”
Section: Smokingmentioning
confidence: 99%
“…The shaded box identifies a small group of participants who were classified as PROP non-tasters at both. Data are from Ahijevych et al [ 57 ] with permission.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations